Implementasi Sistem Informasi Desa Berbasis Web sebagai Upaya Digitalisasi Pelayanan Publik di Desa Tembeng Putik - Ahwan Ahmadi; Martua Hamonangan Nasution; Anisya Putri Wirawan; Moh Dia’uddin Maulidi (Jurnal Teknologi Informasi untuk Masyarakat, 2026)
This community service activity aimed to design and implement a web-based village information system in Tembeng Putik Village to support more effective management and dissemination of village information. The implementation method used a qualitative descriptive approach through several stages: needs analysis, system design, implementation, testing, and monitoring and evaluation. Data were collected through observation, interviews, and document analysis involving village officials and local residents. The system was developed using ReactJS for the frontend, NodeJS and ExpressJS for the backend, and MySQL as the database. The implementation results show that the system can provide centralized village information, including village profiles, population data, education data, health data, village news, activity galleries, and MSME information. The system also helps village officials manage data through an admin page and improves public access to information in a faster, more accurate, and transparent manner. This web-based village information system is expected to enhance public service quality and support sustainable village digitalization.